Wind dancer - Fillmore, Bryce; Tremblay, Ray, 1926-; Clyde, Graig; Hennessy, James; Keith, Brian, 1921-; Harris, Mel, 1957-; McCoy, Matt.; Majestic Entertainment; Sunset Hill Partners LP.; Program Power Entertainment (Firm) ([S.l.] Program Power Entertainment Distributed by Navarre Corporation and Program Power Entertainment, 2000)
When a riding accident leaves a young girl unable to walk, her widowed father seeks help from a renowned and beautiful therapist who used animals to help people. But the girl must first learn to trust the doctor and so must her father.
Feature (90:00) -- Bonus featurettes (29:00).
Includes original theatrical trailer.
Durations: 90:00; 29:00.
Originally released as a motion picture at 1995.
At head of title on disc: Family outdoor adventures.
Produced by Bryce Fillmore and Ray Tremblay ; edited by Steven Johnson ; story by Craig Clyde, James Hennessy, Troy Rohovit ; screenplay by Craig Clyde and James Hennessy.
Brian Keith, Mel Harris, Matt McCoy.
Keywords: Feature films